Alih Kode dan Campur Kode dalam Film Ali & Ratu Ratu Queens - Fatiha, Putri; Agustina (Persona: Kajian Bahasa dan Sastra, 2023)
This research aims to describe the types of use of code switching and code mixing, the factors that cause code switching and codel mixing, andl the function of codel switching andl code mixingl in thel film Ali & Ratu Ratu Queens. This research uses descriptive qualitative methods. The object of this research is the dialogue that leads to code switching and code mixing in the film Ali & Ratu Ratu Queens, which consists of 49 data. Data collection was carried out using the listening method, using advanced techniques in the form of (1) note-taking techniques and (2) data transcription techniques. The results of the research show that (1) the type of code switching used in the film Ali & Ratu Ratu Queens consists of two forms, namely internal code switching and external code switching, (2) the causal factors that occur are, the place and time the speech is carried out, the mode of conversation, and topic of conversation, (3) the functions that occur, namely, explaining, asking, confirming, and reminding. The use of code mixing consists of two types, namely internal code mixing and external code mixing, the factors that cause code mixing in the film Ali & Ratul Ratu Queens are speaker factors, and linguistic factors, and finally the function of code mixing in the film Ali & Ratu Ratu Queens, namely accuracy of meaning or feeling, argumentative, persuasive, short and easy to pronounce, and polite and polite.